PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, KOLABORASI, DAN HASIL PRODUK SOLAR OVEN PESERTA DIDIK KELAS IV SEKOLAH DASAR DI KECAMATAN RANCASARI KOTA BANDUNG - Resti Fitriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the application of Project-based learning (PjBL) modelin improving critical thinking skills, collaboration, and product results solar oven offourth grade elementary school students in IPAS subjects with the theme ofEnergy Sources. The research used a quasi experiment method, where learnerswere divided into two groups: the experimental class (project-based learningmodel) and the learning model applied to the control class. The research subjectswere 34 students from SD Negeri 263 Rancaloa (experimental class) and 30students from SD Negeri 131 Cijawura (control class). The results showed asignificant increase in critical thinking skills in the experimental class compared tothe control class. The average difference between pretest and posttest scores inthe experimental class was 21.17, while the control class was only 17.33, with asignificance value of 0.000 (<0.05). In addition, collaboration skills in theexperimental class showed the majority of students (73.5%) were in the moderateto very high category, while in the control class the majority of students (53.3%)were in the low to very low category. The learners final products in theexperimental class also showed better quality. Three groups were in the highcategory, two groups in the medium category, and one group in the low category.Factors such as material understanding, creativity, and coordination betweenmembers affect the quality of the products produced. From the results of theanalysis, the application of the Project-based learning model proved effective inimproving students critical thinking skills, collaboration, and product quality.